2008
DOI: 10.1175/2007jamc1577.1
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Typhoon Structures Using Advanced Microwave Sounding Unit Data and Its Application to Prediction

Abstract: In this study, the Advanced Microwave Sounding Unit (AMSU) data are used to retrieve the temperature and velocity fields of typhoons and assimilate them with the three-dimensional variational data assimilation (3DVAR) routines for uses in numerical model predictions for typhoons. The authors' procedure of an end-to-end typhoon prediction using an AMSU-based initial condition is similar to the framework developed by Zhu et al. in 2002 but differs from it by considering a downward integration approach in part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Flooding and increased soil moisture will also lead to additional gravity changes. Therefore, the gravity changes due to typhoons detected at HS can be used to validate models of density distribution within a typhoon system, e.g., the model of Chou et al [2008] that is based on three‐dimensional variational data assimilation (3DVAR) and the Advanced Microwave Sounding Unit (AMSU) data.…”
Section: Atmospheric Pressure Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Flooding and increased soil moisture will also lead to additional gravity changes. Therefore, the gravity changes due to typhoons detected at HS can be used to validate models of density distribution within a typhoon system, e.g., the model of Chou et al [2008] that is based on three‐dimensional variational data assimilation (3DVAR) and the Advanced Microwave Sounding Unit (AMSU) data.…”
Section: Atmospheric Pressure Effectmentioning
confidence: 99%
“…In addition to the spatial and temporal scales that result in different admittances for the typhoon and nontyphoon conditions, other factors may also affect the admittance during a typhoon, for example, the actual density of the central part of a typhoon. A typical Doppler radar image of typhoon (see, e.g., the real‐time radar images at Central Weather Bureau of Taiwan) shows that the precipitating water is not evenly distributed within the effective area of a typhoon and the convection within a typhoon can be asymmetric [see, e.g., Chou et al , 2008; Li et al , 2008]. In particular, condensation of water vapor contained in the moist air normally occurs at low altitudes.…”
Section: Atmospheric Pressure Effectmentioning
confidence: 99%
“…Among many studies, different methods have been used to improve the initial typhoon vortex, e.g., the vortex surgery method (Kurihara et al 1993(Kurihara et al , 1995, re-implantation of the model integrated vortex (e.g., Liu et al 1997), a powerful physical initialization scheme with complementary observations (Krishnamurti et al 1993), the inclusion of a Rankine vortex in the background analysis or by assimilation of 3DVAR (Xiao et al 2006(Xiao et al , 2009Chen 2007;Chou et al 2008;Hsiao et al 2010), bogus data assimilation (BDA) using 4DVAR Zou and Xiao 2000;Pu and Braun 2001;Park and Zou 2004;Wu et al 2006), or the recently developed method using an Ensemble Kalman Filter (EnKF) (e.g., Chen and Snyder 2007;Wu et al 2010a;Yen et al 2011). The insertion of a stronger vortex may help improve cyclone intensity forecasting since the model initial cyclone better captures the observed intensity and position.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al (2014) revealed the cold-air intrusion from the northwest played a key role in the big turn of Megi through its adjustment to the large-scale circulation. In the lower layers, the northerly inflow of cold air tends to destroy the axisymmetric thermal structure of the TC, which may reduce the moving speed of the TC (Chou et al, 2008). Chen et al (1997) revealed that the asymmetry of the thermal structure and the strength of the thermal instability layer of the TCs could lead to the significant anomaly of the TC track.…”
Section: Introductionmentioning
confidence: 99%